Scientific Library of the Main Botanical Garden named after N. V. Tsitsin: history, the current state and prospects - E. V. Tkacheva (Библиосфера, 2013)
The history of establishment and development of the scientific library in the Main botanical garden of Russian academy of sciences is described. The acquisition of funds, organization and special features of the library catalogues are considered.